Towards Inclusive Digital Public Services: Policy Directions for Digital Inclusion of the Elderly in Klaten Regency - Setiawan, Abdul Yani; Handoko, V. Rudy; Rochim, Achluddin Ibnu (Kirana Publisher (KNPub), 2025)
The digital transformation of public services in Indonesia has advanced significantly, yet it remains insufficiently inclusive, particularly for older adults who face a heightened risk of digital exclusion. This study investigates the direction of digital inclusion policy for the elderly in Klaten Regency, where the aging population continues to rise. Employing a qualitative approach with an exploratory case study design, data were collected through document analysis, in-depth interviews with key stakeholders, and participatory observation in five digitally oriented villages. Findings reveal that although digital service infrastructure has been developed, no explicit affirmative policy currently addresses elderly participation in digital public services. Most older adults encounter barriers related to digital access, literacy, and limited social support. The analysis is framed using an inclusive policy strategy, policy ecology, and digital inclusion theory. The study concludes that digital policy in Klaten remains technocratic and insufficiently responsive to the needs of vulnerable groups. To realize genuinely inclusive digital public services, the study recommends cross-sectoral collaboration, the formulation of affirmative policies, and the development of community-based digital literacy programs tailored for the elderly.